Efficiency of mixed and rigid occlusal stabilization splints: Randomized clinical trial - Layza Rossatto OPPITZ; Ana Carolina Mastriani ARANTES; Roberto Ramos GARANHANI; Carlos Alberto COSTA; Cristiano Miranda de ARAUJO; Orlando Motohiro TANAKA; Patricia Kern di Scala ANDREIS; Claudia SCHAPPO; Sérgio Aparecido IGNÁCIO; Aline Cristina Batista Rodrigues JOHANN; Rodrigo Nunes RACHED; Elisa Souza CAMARGO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Occlusal stabilization splints are the most common treatment for controlling the deleterious effects of sleep bruxism. This study aimed to evaluate the effectiveness of a low-cost, mixed occlusal splint (MOS) compared to that of a rigid splint. A randomized clinical trial was performed on 43 adults of both sexes with possible sleep bruxism and satisfactory dental conditions. They were divided into rigid occlusal splint (ROS) (n = 23) and MOS (n = 20) groups. Masticatory muscle and temporomandibular joint (TMJ) pain intensity (visual analog scale), quality of life (WHOQOL-BREF), indentations in the oral mucosa, anxiety, and depression (HADS), number of days of splint use, and splint wear were evaluated. All variables were evaluated at baseline (T0), 6 months (T6), and 12 months (T12) after splint installation (T0), and splint wear was evaluated at T6 and T12. Student's t-test, Mann-Whitney U test, non-parametric Friedman's analysis of variance for paired samples and pairwise multiple comparisons, Pearson's chi-square test, two-proportion z-test, non-parametric McNemar's and Cochran's Q, and Wilcoxon tests were used (p < 0.05). In both groups, there was a decrease in TMJ pain and pain intensity over time and improvements in the quality of life scores. At T6, there was a higher rate of splint wear in the MOS group than in the ROS group (p = 0.023). The MOS showed a higher rate of wear than the rigid splint but had similar results for the other variables. Therefore, the use of a mixed splint appears to be effective in controlling the signs and symptoms of sleep bruxism.